Kemampuan Laba Bersih dan Arus Kas Operasi Dalam Memprediksi Arus Kas Masa Depan Pada Perusahaan Manufaktur Subsektor Makanan dan Minuman Yang Terdaftar di Bursa Efekindonesia Periode 2020-2024 - Nasution, Teuku M. Hafis Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The results of this study indicate that net income in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period fluctuated during this period. The net income variable partially has a significant effect on future cash flows. This can be seen from the results of partial hypothesis testing (t-test) which shows a ttable value of 2.01174. Therefore, the tcount value> ttable with a value of 2.040> 2.01174 and a significant value <0.05, namely with a value of 0.047 <0.05. This study shows that net income and cash flow statements in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period fluctuated during this period. The results of this study indicate that net income and operating cash flow have a significant effect on future cash flows. This can be seen from the results of simultaneous testing (F Test) which shows the Fcount value is 43.852 with a significant value of 0.000 (Table F can be seen in Appendix VII). From the F distribution table, the Ftable value is 2.80. Therefore, the Fcount value> Ftable, namely with a value of 43.852> 2.80 and a significant value <0.05, namely with a value of 0.000 <0.05. The test results show that H3 is accepted, which means that the net profit and operating cash flow variables have a significant effect on future cash flows.